(3LeY GdahGFO GdefJNHI ef GdNhGU GdeLQHIs - (3CHh GdeYGdj YHO Gdedc Hf CHj GdYdGA, GHf RgQ GdeJWHH,J (B557 (3g` s
(3ChdgG (B:s
(3eeG LeYg hCTGQ ajg Edi CSeGA ef JbOe ef GdMceGA hZjQge ef GdadGSaI GdYdeGA , EeG HMQa hGMO ef GSeg Gh HMQajf s
(3BNQgG (B:s
(3hjMd dg ZQGA MhJ hjcJHI cdeGJ jbhe HgG GdCfSGf GdeUQhY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B63 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(206(1)) s
Keywords: (3GdWHs